Effect of Milling Time on nanostructured Hydroxyapatite Results Synthesis by Precipitation Method - Pratiwi, Sari; Windarti, Tri; Nurhasanah, Iis (Chem Info Journal, 2013)
A study "Effect of Milling Time on Nanostructured Hydroxyapatite Synthesis Results by Precipitation Method" in purpose to know the effect of milling time on purity, phases and size of hydroxyapatite crystals synthesized. Hydroxyapatite (HA) were synthesized by the method of precipitation by adding dropwise a solution of CaCl2 to a solution of KH2PO 4 which has been conditioned at pH 9 with stirring and heated at 40 Â°C for 4 hours. The resulting suspension was allowed to stand for 20 hours. Product of precipitation milled using a Planetary Ball Mill at 880 rpm angular velocity and the ratio of powder/ballmill 1:10 with milling time variation 0, 5, 15, 30 and 60 minutes. Based on the FTIR and XRD, it was concluded that the HA produced by milling time of 60 minutes has not been able to achieve high purity. Another type of calcium phosphate formed on the product is calcium hydrogen phosphate anhydrous (CHPA). The longer the milling time, the smaller the size of HA crystals. Size of HA crystals are formed on the nanometer scale is 49.85 nm; 38.30 nm; 34.84 nm; 33.44 nm and 30.44 nm.